(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Because 56 ethnic groups together form the big family of the Chinese nation, ethnic minority culture has naturally become an indispensable part of the Chinese nation’s culture. It is the crystallization of the wisdom of ethnic minorities and the spiritual wealth of all mankind. English is one of the most widely spoken languages in the world. The translation of the classics of ethnic minorities spreads the culture of ethnic minorities to the world, so that many people in the world can understand the culture of our ethnic minorities. Of course, this work cannot be completed in a short time. A lot of translators’ efforts are needed. After more than 30 years of development, the modern corpus linguistics discipline team has grown rapidly. At the same time, due to the continuous intervention and mutual agitation of various academic thoughts, they are also constantly changing.